Human resources management in China cases in HR practice - Davies, Doug (Chandos Pub., 2011)
Aimed at people interested in management and Human Resources in China, this book is a collection of original and researched case studies on a variety of HR issues occurring in Chinese organisations, both privately-owned and part of multi-national enterprises, and how these issues are resolved by management. The impacts of the solutions in the organisations are also discussed. Preceded by a brief review of the Chinese and Western literature on this problem, the case is then presented and concluded by an analysis of the situations and solutions implemented.based on original resea.
"The HEAD Foundation: Human Capital & Education for Asia Development"--Cover. - Includes bibliographical references and index. - Print version record
Keywords: Personnel management -- China; Personnel management -- Case studies -- China; Personnel; Direction; Chine; Personnel; Direction; Chine; Études de cas; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; Personnel management; China; Case studies; Études de cas